2006
DOI: 10.1002/ana.21055
|View full text |Cite
|
Sign up to set email alerts
|

Early frontotemporal dementia targets neurons unique to apes and humans

Abstract: Objective: Frontotemporal dementia (FTD) is a neurodegenerative disease that erodes uniquely human aspects of social behavior and emotion. The illness features a characteristic pattern of early injury to anterior cingulate and frontoinsular cortex. These regions, though often considered ancient in phylogeny, are the exclusive homes to the von Economo neuron (VEN), a large bipolar projection neuron found only in great apes and humans. Despite progress toward understanding the genetic and molecular bases of FTD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
240
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 308 publications
(260 citation statements)
references
References 44 publications
16
240
1
3
Order By: Relevance
“…The number of VENs is significantly greater in the postnatal brains relative to the neonatal brains. The percentage of total neurons that are VENs is relatively stable in adulthood (see Tables 2, 3) and is similar to the percentages observed by Seeley et al (2006). Figure 9 illustrates the ratio between the number of VENs in the right hemisphere and that in the left.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The number of VENs is significantly greater in the postnatal brains relative to the neonatal brains. The percentage of total neurons that are VENs is relatively stable in adulthood (see Tables 2, 3) and is similar to the percentages observed by Seeley et al (2006). Figure 9 illustrates the ratio between the number of VENs in the right hemisphere and that in the left.…”
Section: Resultssupporting
confidence: 76%
“…The VENs are also reduced in FI ). In contrast, Seeley et al (2006Seeley et al ( , 2007 found that the VENs were not significantly reduced in Alzheimer's dementia (AD) although a reduction had been reported in an earlier study which did not use stereological methods (Nimchinsky et al 1995). Rankin et al (2006) systematically investigated the capacity for empathic concern in a large population of neurological patients and found that this capacity was greatly reduced in FTD patients; while this capacity was variably expressed in Alzheimer's patients it was not significantly reduced relative to neurologically normal controls.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Highly social species (e.g., elephants, great apes, and dolphins) that exhibit prosocial behaviors such as giving, targeted helping, and consolation behaviors are also those that are capable of complex social‐cognitive acts such as mirror self‐recognition (Seeley & Sturm, 2006). These species are also united in that they have relatively large proportions of von Economo neurons, large neurons that are important for integrating socioemotional cues, which are also especially vulnerable in bvFTD (Seeley et al., 2006). Future work that relates the integrity of these specialized neurons to the degradation of prosociality in bvFTD will help to delineate the biology of these exceptional behaviors.…”
Section: Discussionmentioning
confidence: 99%